1997
DOI: 10.1177/112067219700700409
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in Ocular Hypertension

Abstract: The aim of the study was to determine whether certain factors are related to an increased risk of developing open-angle glaucoma. A total of 345 untreated glaucoma suspects with intraocular pressure (IOP) > or = 21 mmHg, cup to disc ratio 0.4 or less and no visual field defects, were followed up for 6 to 8 years (mean 7.3). During the follow-up 71 patients developed established glaucoma and were compared to the remaining 274 patients. The following factors were analysed: age, family history of glaucoma, IOP, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 30 publications
3
15
0
7
Order By: Relevance
“…In clinical practice it is generally agreed that eyes with far advanced glaucoma are more susceptible to further VF damage than eyes with early glaucoma and therefore need lower target pressures (Wilson et al 1982;Anderson 1989;Shirakashi et al 1993;Stewart et al 1993). The risk of progression increased also with increasing age, a finding supported by previous studies (Kass et al 1980;Armaly et al 1980;Quigley et al 1994;Georgopoulos et al 1997). This study supports lower target pressures in advanced glaucoma and older patients.…”
Section: Discussionsupporting
confidence: 77%
“…In clinical practice it is generally agreed that eyes with far advanced glaucoma are more susceptible to further VF damage than eyes with early glaucoma and therefore need lower target pressures (Wilson et al 1982;Anderson 1989;Shirakashi et al 1993;Stewart et al 1993). The risk of progression increased also with increasing age, a finding supported by previous studies (Kass et al 1980;Armaly et al 1980;Quigley et al 1994;Georgopoulos et al 1997). This study supports lower target pressures in advanced glaucoma and older patients.…”
Section: Discussionsupporting
confidence: 77%
“…Older age has also been found to be an independent risk factor for the progression of OHT. This has been reported in multiple studies [2,4,14,25]. Interestingly, in the OHTS [1,2] African American race was associated with an increased risk of progression from OHT to glaucoma in the univariate but not in the multivariate analysis.…”
Section: Progression From Ocular Hypertension To Primary Open-angle Gsupporting
confidence: 51%
“…Some previous studies have identified cardiac disease, stroke, poor perfusion pressure, hypertension or hypotension as predictive factors for the development of POAG. 26,29,32,44,45 As in diabetes, our ascertainment of these factors was based on patient history without confirmation by chart review or direct testing. A history of heart disease was a statistically significant predictive factor in the pooled univariate analysis but not the multivariate analysis.…”
mentioning
confidence: 99%